Analysis of Good Manufacturing Practices (GMPs) Implementation In Gudeg SMEs to Improve Food Safety Product - Febriana Rias Putri; Rosa Amalia (Agroindustrial Journal, 2022)
Gudeg is one of traditional food prefered by public in Yogyakarta. To meet the standard and quality requirements for Gudeg product the industry is required to be capable of making improvement to production procedure in each flow of its production activities. An analysis of the implementation of GMPs (Good Manufacturing Practices) to Gudeg SMEs in Yogyakarta is deemed important.  It aims to identify the factors of the highest non-conformities and to provide solutions in creating a better food production procedure for Gudeg SMEs in Yogyakarta. The aspects that had the highest incompatibility values were formulated using the 5 Why's Analysis method and Ishikawa diagrams. The research aims: 1) to analyze the implementation of GMPs in one of the SMEs in Gudeg production in Yogyakarta; 2) to analyze the factors of the highest discrepancy with the implementation of GMPs; and 3) to give suggestions for the improvements such nonconformities. The results of the assessment of the implementation of GMPs in Gudeg SMEs showed that the level of GMPs implementation was good with a conformity (93.30%). The highest discrepancy was found in the employee aspect (37.5%) due to the absence of employee training regarding food sanitation and safety in the industry, also the lack of reference standards for the application of GMPs in industry.